Group-based memory rehabilitation for people with multiple sclerosis: subgroup analysis of the ReMiND trial - Martin, Kristy-Jane; Lincoln, Nadina; das Nair, Roshan (Mark Allen Healthcare, 2014)
Background/Aim: Memory problems are frequently reported in people with multiple sclerosis (MS). These can be debilitating and affect individuals and their families. This sub-group analysis focused on the effectiveness of memory rehabilitation in patients with MS. Methods: Data were extracted from a single blind randomised controlled trial, the ReMiND trial, which also included participants with traumatic brain injury and stroke. Participants were randomly allocated to compensation or restitution treatment programmes, or a self-help control. The programmes were manual-based and comprised two individual and ten group sessions. Outcome measures included assessments of memory, mood and activities of daily living. A total of 39 patients with MS participated in this study (ten males (26%), 29 females (74%); mean±SD age: 48.3±10.8 years). Results: Comparison of groups showed no significant effect of treatment on memory, but there were significant differences between compensation and restitution on self-report symptoms of emotional distress at both 5- (p=0.04) and 7-month (p=0.05) follow-up sessions. The compensation group showed less distress than the restitution group. Conclusions: Individuals with MS who received compensation memory rehabilitation reported significantly less emotional distress than those who received restitution. Further research is needed to explore why self-reported memory problems did not differ between groups.